Hammarskjöld : A Life - Lipsey, Roger, 1942- (UPCC book collections on Project Muse., 2013)
After his mysterious death, Dag Hammarskjöld was described by John F. Kennedy as the "greatest statesman of our century." Second secretary-general of the United Nations (1953-61), he is the only person to have been awarded the Nobel Peace Prize posthumously. Through extensive research in little explored archives and personal correspondence, Roger Lipsey has produced the definitive biography of Dag Hammarskjöld. Hammarskjöld: A Life provides vivid new insights into the life and mind of a truly great individual. Hammarskjöld the statesman and Hammarskjöld the author of the classic spiritual journal Markings meet in this new biography, and the reader will meet them both in these pages. A towering mid-twentieth-century figure, Hammarskjöld speaks directly to our time.